How E-Learning Environmental Stimuli Influence Determinates of Learning Engagement in the Context of COVID-19? SOR Model Perspective - Yang, Junhui; Peng, Michael Yao-Ping; Wong, ShwuHuey; Chong, WeiLoong (Frontiers in Psychology, 2021)
The pandemic of COVID-19 at the beginning of 2020 changes the conventional learning mode at schools of most students all over the world, and the e-learning at home becomes a new trend. Taking Chinese college students as the research subject, and drawing on the stimulus-organism-response model (S-O-R model), this paper examines the relationship between the peer referent, perceived closeness and perceived control and the learning engagement. By using data from 377 college students who have used the e-learning, this study show that perceived closeness, perceived control, and peer referent in e-learning have a positive effect on the self-efficacy and well-being of students, thus improving students’ enthusiasm in learning. Our intent is to assist researchers, instructors, designers, and others in identifying effective methods to conceptualize and measure student engagement in e-learning.